Perencanaan Program Tahfizh Al-Qur’an dalam Meningkatkan Kualitas Hafalan di Madrasah Aliyah Negeri 2 Palembang - Kiki Rahma Alya; Ade Akhmad Saputra (Yayasan Al-Afif, 2026)
This study aims to analyze the planning of the tahfizh Al-Qur'an program in improving the quality of student memorization at Madrasah Aliyah Negeri 2 Palembang. This research uses a qualitative approach with a case study type of research. The subjects of the study include the head of the madrasah, the deputy head of the madrasah for the curriculum, the coordinator of the tahfizh program, the tahfizh teacher, and the students. Data collection techniques are carried out through observation, interviews, and documentation. Data analysis uses the Miles, Huberman, and Saldaña model which includes data reduction, data presentation, and conclusion drawn. The results of the study show that the planning of the tahfizh Al-Qur'an program at Madrasah Aliyah Negeri 2 Palembang has been carried out systematically through the preparation of program objectives, memorization targets, learning schedules, determination of memorization methods, and the preparation of a learning evaluation system. The memorization target for regular students is set at least 3 juz, namely Juz 30, Juz 1, and Juz 2 which are listed in the student's tahfizh book. The implementation of the program is carried out through intracurricular and extracurricular activities. The learning methods used are the sorogan and muraja'ah methods. The evaluation system is carried out through daily assessments using tahfizh books with indicators of tajweed, fashahah, accuracy, and fluency of memorization, as well as follow-up evaluation in the form of tahfizh exams, munaqosah, and tahfizh graduation which are optional according to the readiness of students. Obstacles in the implementation of the program include diverse student motivations, differences in basic ability to read the Qur'an, lack of consistency in muraja'ah, and limited learning time. This study shows that structured tahfizh program planning is able to make a positive contribution in improving the quality of students' memorization